APPLICATION OF INTEGRATED LEARNING MODEL CONNECTED WITH AUDIOVISUAL MEDIA TO IMPROVE STUDENT LEARNING OUTCOMES AT SMKN 4 JEMBER - Fatmawati, Diah (Journal of Education Technology and Inovation, 2022)
Student learning outcomes to date are still less than what the teacher expects, it is time for teachers to fix the learning process, especially Civics, especially regarding the models, approaches, or techniques used in learning. Several kinds of learning models are expected to be able to overcome problems in Civics learning, including the Connected Model Integrated Learning This research is a Classroom Action Research (CAR) which was conducted in two cycle stages. Cycle I consisted of two meetings and cycle II consisted of one meeting. Each cycle consists of four stages, namely planning, implementing actions, observing and reflecting, The subjects in this study were students of class XI MM1 SMKn 4 Jember, totaling 41 students. The indicator of success in this study is if 75% of students are actively involved in learning and there is also an increase in learning outcomes in each cycle through the post test and if 85% of students can achieve the Minimum Completeness Criteria (KKM) determined by the school, which is 77. The results showed that with the application of the treasure hunt method through the articulation learning model in Civics subjects, the material for Implementation of Democracy in Indonesia in class XI MMI 1, the overall score of student learning activities on each indicator increased by 14.97%, from the average cycle I. by 73.61% to 81.94% in the second cycle. Increased mastery of student learning outcomes increased from the first cycle of 21 students (58.3%) to 31 students (86.1%) who achieved the KKM score in the second cycle